Intuitions of 9th grade pupils about independent events - Correia, Paulo Ferreira; Fernandes, José Antônio (Universidade Estadual de Campinas, 2014)
This paper aims at describing some results of a study about intuitive ideas of independence of pupils attending the 9th grade. In the study participated 310 pupils of the 9th grade, who answered a questionnaire with several tasks on conditional probability and independence. In this paper we explore just the two tasks that involve independence. In general, the results show that students have intuitive ideas about the concept of independence in the contexts studied.